2017
DOI: 10.1016/j.jastp.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Searching for effects caused by thunderstorms in midlatitude sporadic E layers

Abstract: Possible thunderstormsporadic E (Es) layer coupling effects are investigated during two measurement periods, one in 2013 and one in 2014. The analysis was based on ionospheric observations obtained from a Digisonde at Pruhonice, the Czech Republic, an ionosonde at Nagycenk, Hungary, and a 3.59 MHz five-point continuous HF Doppler system located in the western part of the Czech Republic. The latter is capable of detecting ionospheric wave-like variations caused by neutral atmospheric waves generated by thunders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…It shows the similar tendency of tide-period height. With the decrease in the Es height below 100 km and the occurrence of the maximum neutral Na layer during thunderstorms, a remarkable reduction of relative foEs and then disappearance of the Es with a decrease in occurrence rate are observed, as reported in Barta et al (2017). Furthermore, Figure 2b shows the Es height is controlled not only by the diurnal tide but also by the semidiurnal tide.…”
Section: Interactive Commentsupporting
confidence: 55%
See 3 more Smart Citations
“…It shows the similar tendency of tide-period height. With the decrease in the Es height below 100 km and the occurrence of the maximum neutral Na layer during thunderstorms, a remarkable reduction of relative foEs and then disappearance of the Es with a decrease in occurrence rate are observed, as reported in Barta et al (2017). Furthermore, Figure 2b shows the Es height is controlled not only by the diurnal tide but also by the semidiurnal tide.…”
Section: Interactive Commentsupporting
confidence: 55%
“…The atmospheric tide is a dominant dynamical process in the MLT and plays dominant roles in the formation and dynamical processes of the intensification of metallic layered phenomena above thunderstorms." 2/ Page 2. line 15.: Barta et al 2015 performed Superposed Epoch Analysis (SEA) Barta, V., Pietrella, M., Scotto, C., Bencze, P., Sátori, G., (2015) Thunderstorm-related variations in the sporadic E layer around Rome, Acta Geodaetica et Geophysica, 50:261-270 However, Barta et al 2017 reported two case studies which was based on highly sampled ionosonde data, Doppler measurement, and ligthning and TLE records. Thus it was a different type of analysis than the previously reported studies, which based on Superposed Epoch Analysis.…”
Section: Interactive Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…It was the first paper to reveal an enhancement of E s layer which occurs ∼6 h and ∼30 h after lightning. After that, more studies applied the same methodology of SEA on lightning and E s layer measurements using the hourly lightning events as trigger times (Johnson and Davis, 2006;Davis and Lo, 2008;Barta et al, 2013;Yu et al, 2015;Barta et al, 2017). Nowadays, the mechanism responsible for the ionospheric E s perturbations above thunderstorms is not well understood.…”
mentioning
confidence: 99%